Impacts of university lockdown during the coronavirus pandemic on college students’ academic achievement and critical thinking: A longitudinal study - Lv, Xiaojing; Ma, Juanjuan; Brinthaupt, Thomas M.; Zhao, Shaochun; Ren, Xuezhu (Frontiers in Psychology, 2022)
The outbreak of the coronavirus disease 2019 (COVID-19) has resulted in widespread university lockdown. However, impacts of the university lockdown on the learning and academic development of university students have not been thoroughly investigated. The current study examined college students’ changes of learning outcomes during the COVID-19 lockdown period and clarified what might explain individual differences in students’ learning outcomes after they had learned from home for a whole semester when universities were physically closed due to the COVID-19 pandemic. Data were derived from a longitudinal study examining the development of college students including students’ academic achievement and critical thinking (including both skills and dispositions) before and after the university lockdown. We observed significant decreases in critical thinking skills and dispositions from pre- to post-lockdown. Both perceived academic achievement and critical thinking exhibited greater variability after the lockdown. In addition, students’ readiness for online learning, especially their self-management skills, consistently predicted post-lockdown learning outcomes after controlling for pre-lockdown outcomes and family socioeconomic status (SES). Those who have assumed more responsibilities at home, or who were more vulnerable to emotional distress during the pandemic, performed less well in post-lockdown learning outcomes. These findings call for better management of student learning and development when major changes are required in higher education practices for responding to the ongoing COVID-19 crisis as well as other potential situations.